Identification of Bioactive Compounds in Polar and Nonpolar Extracts of Araujia sericifera - Palomino-Schätzlein, Martina; Montaño, Mary Cecilia; Escrig, Pablo V.; Boira, Herminio; Corma, Avelino; Pineda-Lucena, Antonio; Primo, Jaime; Cabedo, Nuria (Planta Medica International Open, 2017)
Araujia sericifera is a native perennial, climbing laticiferous shrub from South America that is currently naturalized in many other countries. Previous data describe promising properties for A. sericifera, but no systematic study of its bioactive compounds and possible medicinal applications has been conducted to date. In the present study, aerial parts of A. sericifera (leaves, stems, and fruits) were explored by combining GC-MS and NMR spectroscopy analysis for both nonpolar (hexane) and polar (methanol) extracts. The hexanic extracts contained high amounts of pentacyclic triterpenes including two new metabolites, 3-tigloyl germanicol (18) and 3-tigloyl lupeol (19). The methanolic extracts revealed the presence of luteolin-7-glucoside (24), trigonelline (22), and conduritol F (23) as the main constituents. A multivariate study of a meaningful number of extracts allowed us to determine the distribution of compounds inside the plant. A cytotoxic evaluation in vitro showed that both leaf and fruit hexanic extracts presented a moderate activity against human breast carcinoma cell lines (MDA-MB-453 and MCF-7) and human colon carcinoma cell line (HCT-116) by the MTS [3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium] assay.
Keywords: Araujia sericifera; Asclepiadaceae; metabolite profile; cancer cell lines; GC-MS; NMR spectroscopy